2020
DOI: 10.1016/s2214-109x(20)30062-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of dementia risk in low-income and middle-income countries (the 10/66 Study): an independent external validation of existing models

Abstract: Background To date, dementia prediction models have been exclusively developed and tested in high-income countries (HICs). However, most people with dementia live in low-income and middle-income countries (LMICs), where dementia risk prediction research is almost non-existent and the ability of current models to predict dementia is unknown. This study investigated whether dementia prediction models developed in HICs are applicable to LMICs. MethodsData were from the 10/66 Study. Individuals aged 65 years or ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 27 publications
2
58
0
Order By: Relevance
“…The cognitive capital of a country is also crucial for its economic prosperity because it enables populations to pivot more adeptly and adaptively in the face of economic shocks, rapid technological change, and environmental challenges ( 4 , 5 ). An absence or reduction of such a flexible mindset leads to economic and social deterioration that will worsen mental and physical well-being ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive capital of a country is also crucial for its economic prosperity because it enables populations to pivot more adeptly and adaptively in the face of economic shocks, rapid technological change, and environmental challenges ( 4 , 5 ). An absence or reduction of such a flexible mindset leads to economic and social deterioration that will worsen mental and physical well-being ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…These authors [14] offer an explanation of their results that may also extend to our findings. [20,42,13,43]; ANU-ADRI: 0.49 to 0.78 [44,42,13], DRS: 0.56 to 0.84 [18,13]). Among the risk scores assessed, the ANU-ADRI had the poorest discrimination accuracy (AUC 0.45 in WHII) relative to the UKB-DRS.…”
Section: Discussionmentioning
confidence: 98%
“…Further, these cohorts are predominately Caucasian, based in the UK, and are less likely to live in socioeconomically deprived areas than the general population [48,16]. Given that a recent study showed that not all dementia risk models developed in high-income countries are applicable to low and middle-income countries [42], we emphasise the need to evaluate the UKB-DRS across a diverse range of cohorts before translating it for use in routine care. Second, with respect to other existing risk models, this study (and several others) has shown that while dementia risk scores may have good-tomoderate performance in their development cohorts, they typically have reduced predictive accuracy when applied under different settings.…”
Section: Strengths and Limitations……………………………………………………………………………………mentioning
confidence: 99%
“…1 However, the greatest increase in the number of people with dementia will be in developing countries, 2 for which research on dementia is often limited or non-existent. Blossom Stephan and colleagues' study 3 in The Lancet Global Health fills this research gap. The authors selected five dementia risk prediction models developed in HICs and assessed their validity in low-income and middle-income countries (LMICs), using data from the 10/66 Study.…”
Section: Challenges In Dementia Risk Prediction In Low-income and Midmentioning
confidence: 99%